Race-Ethnic Differences of Sleep Symptoms in an Elderly Multi-Ethnic Cohort: The Northern Manhattan Study - Ramos, Alberto R. (S. Karger AG, 2011)
BACKGROUND: Sleep disorders are associated with stroke and may vary among elderly Hispanics, Blacks and Whites. We evaluated differences in sleep symptoms by race-ethnicity in an elderly population-based urban community sample. METHODS: Snoring, daytime sleepiness and reported sleep duration were ascertained by standardized interviews as a part of the Northern Manhattan Study, a prospective cohort study of vascular risk factors and stroke risk in a multi-ethnic urban population. Sleep symptoms were compared amongst race-ethnic groups using logistic regression models. RESULTS: A total of 1,964 stroke-free participants completed sleep questionnaires. The mean age was 75 ± 9 years, with 37% men, with 60% Hispanics, 21% Blacks and 19% Whites. In models adjusted for demographic and vascular risk factors, Hispanics had increased odds of frequent snoring (odds ratio, OR: 3.6, 95% confidence interval, CI: 2.3–5.8) and daytime sleepiness (OR: 2.8, 95% CI: 1.7–4.5) compared to White participants. Hispanics were more likely to report long sleep (≥9 h of sleep, OR: 1.8, 95% CI: 1.1–3.1). There was no difference in sleep symptoms between Black and White participants. CONCLUSION: In this cross-sectional analysis among an elderly community cohort, snoring, sleepiness and long sleep duration were more common in Hispanics. Sleep symptoms may be surrogate markers for an underlying sleep disorder which may be associated with an elevated risk of stroke and may be modified by clinical intervention.